Professores Especialistas em Currículo (PEC) na formação permanente de professores na rede de ensino estadual de São Paulo: atuação e competências - Lima, Silvia Aparecida de Jesus (2023)
Introduction: This dissertation is part of the Education: Curriculum course in the area of Educator Training, having as an interest and subject of research the Curriculum Specialist Teachers (PECs) of the Education Department of the State of São Paulo, who act as teacher trainers seeking to put into practice the curriculum of the teaching network. The research aims to answer the following question: Who are the teacher trainers of the teaching network - state - in São Paulo? The general objective of the research is to identify the profile, attributions, strategies, methodologies and competences in acting as trainers of Elementary School II and Secondary School teachers in the Education Directorates of the state network of São Paulo. For the development of this study, a predominantly qualitative approach will be adopted as methodological procedures CHIZZOTTI (2014), GIL (2002) and CRESWEL (2014). The analysis of the information will be based on bibliographic research, document research, questionnaire and online interviews. Results: We believe that this research is relevant, as the data collected can serve as inputs/knowledge in order to contribute to the improvement of continuing education carried out by the PECs in the network